0=(4x-1)(x-1)

Simple and best practice solution for 0=(4x-1)(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=(4x-1)(x-1) equation:


Simplifying
0 = (4x + -1)(x + -1)

Reorder the terms:
0 = (-1 + 4x)(x + -1)

Reorder the terms:
0 = (-1 + 4x)(-1 + x)

Multiply (-1 + 4x) * (-1 + x)
0 = (-1(-1 + x) + 4x * (-1 + x))
0 = ((-1 * -1 + x * -1) + 4x * (-1 + x))
0 = ((1 + -1x) + 4x * (-1 + x))
0 = (1 + -1x + (-1 * 4x + x * 4x))
0 = (1 + -1x + (-4x + 4x2))

Combine like terms: -1x + -4x = -5x
0 = (1 + -5x + 4x2)

Solving
0 = 1 + -5x + 4x2

Solving for variable 'x'.

Combine like terms: 0 + -1 = -1
-1 + 5x + -4x2 = 1 + -5x + 4x2 + -1 + 5x + -4x2

Reorder the terms:
-1 + 5x + -4x2 = 1 + -1 + -5x + 5x + 4x2 + -4x2

Combine like terms: 1 + -1 = 0
-1 + 5x + -4x2 = 0 + -5x + 5x + 4x2 + -4x2
-1 + 5x + -4x2 = -5x + 5x + 4x2 + -4x2

Combine like terms: -5x + 5x = 0
-1 + 5x + -4x2 = 0 + 4x2 + -4x2
-1 + 5x + -4x2 = 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-1 + 5x + -4x2 = 0

Factor a trinomial.
(-1 + x)(1 + -4x) = 0

Subproblem 1

Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(1 + -4x)' equal to zero and attempt to solve: Simplifying 1 + -4x = 0 Solving 1 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -4x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = 0 + -1 -4x = 0 + -1 Combine like terms: 0 + -1 = -1 -4x = -1 Divide each side by '-4'. x = 0.25 Simplifying x = 0.25

Solution

x = {1, 0.25}

See similar equations:

| a=3.14(63)(63) | | 3x+2y=152 | | c=2(3.14)(126) | | 55x-14-35x=-133 | | 90x-1400-x^2=0 | | (X^6)^6/x^3 | | 48x-13-24x=-358 | | y=(x^2-8x+12)(x+1) | | (4/3)(3.14) | | -12(x+6)=4(x+6) | | a=3.14(13)(13) | | x+(x*2.24)=2200 | | c=2(3.14)(26) | | -13-3(t-5)= | | Logx=(x^2-12) | | X*2-6x-23=0 | | 15x+53=83 | | 37x-14+19x=-105 | | .04x+.07(11000-x)=660.00 | | a=3.14(17)(17) | | x+(x*1.88)=2200 | | a=3.14(17) | | c=43.69cm | | 13x+-19x=154 | | x^3-9x^2+81x+621=0 | | 20y^2-16x^2-320=0 | | ln(8x+17)=ln(5-x^2) | | 2x-3x=-4x | | sin(2x)+cos(3x)=0 | | c=2(3.14)(34) | | 33x-10=180 | | 6h+3=33 |

Equations solver categories